Previous archaeological excavations along the 'Ostlänken' Railway Corridor 1965:2012: Early Iron Age graves at Gerstaberg - Swedish National Heritage Board UV Mitt (Uppsala University, 2016)
In October 1987, a small cemetery at Gerstaberg, Ytterjärna parish, Södermanland, was investigated & removed (Ancient monument 185). The excavation was preceeded by a trial excavation in order to establish whether the monuments were indeed ancient. Existing records showed a mound-like and a stone-setting-like structure.

The trial excavations revealed that the mound-like structure was modern, while the stone-setting like structure was in fact a group of burials, consisting of a square stone-setting and two or three smaller stone-settings. The subsequent investigation brought to light further burials, bringing the total to 17.

All graves has cremation burials, although the mode of burial was varied. Osteological analyses brought forth that all burials were adult, though none could be sexed. Four features lacked burials, and may have been children's graves. One feature (A18) may not have been a grave at all.

Burial assemblages consisted mainly of pottery, both as bone receptacles and as subsidiary vessels. The pottery is of typical Iron Age type.

The graves were dated to the Early Iron age, possibly used by one family, although this could not be confirmed. The cemetery is part of a small Iron Age complex.

Purpose:

The aim of the investigation was to explore a fairly small cemetery at Gerstaberg, Ytterjärna parish, Södermanland. The excavation was occasioned by the planned construction of a new service road over the railway line to the country mansion. The excavation was preceeded by a trial excavation to establish whether the recorded features were indeed ancient monuments.

The ZIP-file contains two Shape files with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as a geo-referenced map (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Under tolv dagar i oktober 1987 undersöktes och borttogs ett mindre gravfält vid Gerstaberg, Ytterjärna socken, Södermanland (fornlämning 185). Undersökningen genomfördes med anledning av planerad utbyggnad av en ny anslutningsväg över järnvägen till herrgården. Undersökningen föregicks av en förundersökning. Anläggningarna bestod av en hög- och stensättningsliknande lämning, som betecknades vara sannolika naturbildningar.

Vid förundersökningen konstaterades den högliknande lämningen vara en sentida hög. Den stensättningsliknande lämningen visade sig vara en gravgrupp bestående av en kvadratisk stensättning och 2-3 mindre stensättningar.

Vid den därpå följande undersökningen påträffades ytterligare anläggningar , sammanlagt 17 stycken.

De undersökta gravarna daterades till den äldre järnåldern.

Datamaterialet från undersökningen sammanställdes och harmoniserades vid Uppsala universitet under 2014 . Detta skedde på uppdrag av Trafikverket samt Länsstyrelserna i Östergötland, Södermanland och Stockholms län, i ett projekt med syfte att sammanställa arkeologiska undersökningar och utredningar inom den beslutade korridoren för Ostlänken samt den närmsta omgivningen.

Syfte:

Syftet med den arkeologiska undersökningen var att utreda ett mindre gravfält vid Gerstaberg, Ytterjärna socken, Södermanland. Undersökningen genomfördes med anledning av planerad utbyggnad av en ny anslutningsväg över järnvägen till herrgården. Undersökningen av fornlämning 185 föregicks av en förundersökning för att kunna fastställa om de tegistrerade anläggningarna var fornlämningar.

ZIP-filen innehåller data i form av två shape-filer med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt en georefererad karta (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Gravar från äldre järnålder vid Gerstaberg
Keywords: Early Iron Age; äldre järnålder; HISTORY; HISTORIA; Archaeology; Arkeologi